MORAL VALUES OF THE MAIN CHARACTERS DEPICTED IN NOVEL ENTITLED “BOUND” BY OKKY MADASARI - Maria Maria; Baginda Simaibang; Magdad Hatim (ELTE Journal (English Languange Teaching and Education), 2020)
Abstract: The purposes of this study were (1) to find out what moral values found in the novel “Bound” by Okky Madasari and (2) to describe the intrinsic elements of the novel. The method used was descriptive qualitative. Data collection was done by using documentation, book reviewer, and expert interview. The validity of the data used in this study was the triangulation theory. The data analysis technique in this study was done with qualitative data analysis techniques. The results of the study indicated that (1) The moral values of the main character, contained in the novel “Bound” by Okky Madasari were divided into moral value of humanity, the moral value of the social, moral value of justice, and moral value of religion, ad (2) the intrinsic elements of this novel consists of a plot, setting, character, and characterization. The plot used in the novel “Bound” is advanced. Keywords: novel Bound, intrinsic elements, moral values, triangulation